2015
DOI: 10.1097/jto.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Large-Cell Neuroendocrine Carcinoma: From Epidemiology to Therapy

Abstract: Lung neuroendocrine tumors are a heterogeneous subtype of pulmonary cancers representing approximately 20% of all lung cancers, including small-cell lung cancer (SCLC) and large-cell neuroendocrine carcinoma (LCNEC). The frequency appears to be approximately 3% for LCNEC. Diagnosis of LCNEC requires attention to neuroendocrine features by light microscopy and confirmation by immunohistochemical staining for neuroendocrine markers. Both SCLC and pulmonary LCNEC are high-grade and poor-prognosis tumors, with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
251
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(267 citation statements)
references
References 72 publications
9
251
0
7
Order By: Relevance
“…However, some authors suggested that low and high-grade neuroendocrine tumours do not represent the continuum of the same lesion [32]. In our study, in LCNEC patients lymph node status, but not nestin expression, was associated with shorter survival.…”
Section: Discussionsupporting
confidence: 50%
“…However, some authors suggested that low and high-grade neuroendocrine tumours do not represent the continuum of the same lesion [32]. In our study, in LCNEC patients lymph node status, but not nestin expression, was associated with shorter survival.…”
Section: Discussionsupporting
confidence: 50%
“…However, an increasing body of knowledge is accumulating in lung NET about biomarkers with predictive value, which could modify the therapy of these tumors in near future. This holds true especially for TC and AC where treatment, when non directly surgical (as mainly happens), relies on multimodality approaches or non-conventional drugs, whilst LCNEC and SCLC are generally cured by exclusive chemo-radiotherapy 87,88 .…”
Section: Predicting In Netmentioning
confidence: 99%
“…PCI in patients with ES-SCLC reduces the incidence of brain metastasis, but the impact on overall survival is controversial [20, 21]. The role of TRT and PCI in local or advanced LCNEC remains undefined [6, 22, 23]. …”
Section: Introductionmentioning
confidence: 99%